Методика відбору системи показників для ідентифікації стану комп'ютерної системи - Гавриленко, Світлана Юріївна (Національний аерокосмічний університет ім. М. Є. Жуковського "Харківський авіаційний інститут", 2019)
Процеси проектування, розробки, тестування, супроводу та управління сучасними комп’ютерними системами (КС) вимагають вирішення завдань оптимізації в умовах отримання багатьох характеристик в режимі реального часу. При цьому однією з пріоритетних задач є задача відбору цих характеристик або показників. Предметом вивчення в статті є методи оцінки інформативності показників функціонування комп’ютерної системи. Метою є розробка методики відбору системи показників для ідентифікації стану комп’ютерних систем за умови нечітких вихідних даних. Для автоматизації процесу вибору найбільш впливових показників необхідно залучення додаткової інформації, щодо впливовості окремих показників та ефективних математичних рішень оброки нечітких даних, що зможе підвищити достовірність результатів ідентифікації стану КС. Це обумовлює актуальність задачі розробки методики відбору системи показників для ідентифікації стану КС. Результати. Проведений аналіз показав, що завдання ідентифікації розпадається на дві підзадачі: вибір сукупності контрольованих показників об'єкта та рішення відповідно завдання ідентифікації. Розглянуто вирішення задачі вибору підмножини інформативних параметрів із множини параметрів, які оцінюються з використання «відстані» Кульбака. Відзначено, що ця технологія базується на припущенні, що щільності параметрів системи, які контролюються, відомі та можуть бути статистично оцінені для кожного із станів системи. В реальних умовах малої вибірки вихідних даних, ця гіпотеза не може бути коректно обґрунтована. В цих умовах природно використовувати інші можливості для опису невизначеності вихідних даних, не використовуючи при цьому математичний апарат теорії ймовірності. Виходячи із цього, сформовані вимоги до критерію інформативності. Показано, що цим вимогам задовольняє математичний апарат нечіткої математики, на базі якого сформована відповідна методика. Висновки. Розроблено методику відбору системи показників для ідентифікації стану комп’ютерної системи. Основною відмінністю цієї методики є введення нового критерію оцінки інформативності за умови нечітких вихідних даних, що підвищує точність ідентифікації стану КС.

The processes of design, development, testing, maintenance, and management of modern computer systems (CS) require the solution of optimization tasks. The peculiarity of such processes is to obtain many characteristics in real time. At the same time, one of the priority tasks is the task of selecting these characteristics or indicators. The subject of the article study is method for evaluating the informativeness of the indicators of the functioning of computer systems. The purpose of the article is to develop a methodology for selecting a system of indicators for identifying the state of the CS under the condition of fuzzy output data. To automate the process of choosing the most influential indicators, it is necessary to involve additional information. Information is needed on the impact of individual indicators and effective mathematical decisions on false data cessation. This information can increase the reliability of the results of the identification of the state of the CS. This determines the relevance of the task of de-veloping a methodology for selecting a system of indicators for identifying the state of the CS. Results. The analysis showed that the identification problem falls into two subtasks. The first is the choice of a set of monitored indicators of an object. The second is the solution for the identification task accordingly. The solution to the problem of choos-ing a subset of informative parameters from a set of parameters controlled by using the "distances" of Kulbak is considered. This technology requires the following assumption. The densities of system parameters that are moni-tored are known. They can be statistically evaluated for each state of the system. In real conditions of a small sample of output data, this hypothesis cannot be properly justified. In these circumstances, it is natural to use other possibili-ties to describe the uncertainty of the output data. At the same time, it is not desirable to use the mathematical appa-ratus of probability theory. Proceeding from this, the requirements for the informative criterion are formed. It is shown that these requirements are met by a mathematical apparatus of fuzzy mathematics. On the basis of this appa-ratus, an appropriate method is formed. Conclusions. The method of selection of the system of indicators for the identification of the state of the computer system is developed. This allowed us to expand the range of incoming processed metrics in the state identification system on the condition of fuzzy input data and improve the accuracy of identifying the state of the CS.
The indicators' system selection method for the computer system status identification
Keywords: комп'ютерна система; ідентифікація стану; оцінки інформативності; "відстань" Кульбака; computer system; state identification; estimation of informality; "distance" of Kulbak